Strategi Pembelajaran Inklusif Dalam Mendukung Chinldren Well-Being Anak Berkebutuhan Khusus di PAUD - Naila Chofia Salsabila; Taopik Rahman; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to examine inclusive learning strategies in supporting the children’s well-being of children with special needs in Early Childhood Education. Children’s well-being includes emotional, social, and optimal child development within a safe and enjoyable learning environment. This study uses a literature review approach by analyzing various relevant books and journal sources. The inclusive learning strategies applied include differentiated instruction, individualized approaches according to children's needs, the use of varied learning media, as well as collaboration between teachers and parents. The results of the study indicate that these strategies are able timprove self-confidence, social interaction, and learning engagement of children with special needs. Therefore, inclusive learning plays an important role in supporting children’s overall well-being